Dynamics of the Zones of Strong Earthquake Epicenters in the Arctic–Asian Seismic Belt - Lyudmila P. Imaeva; Valery S. Imaev; Boris M. Koz’min (Geosciences, 2019)
Our comprehensive study of the Russian Arctic region aims to clarify the features and types of seismotectonic deformation of the crust in the Arctic–Asian Seismic Belt, specifically in the zones of strong earthquakes in the Laptev Sea Segment, the Kharaulakh Segment, and the Chersky Seismotectonic Zone. We have analyzed modern tectonic structures and active fault systems, as well as tectonic stress fields reconstructed by tectonophysical analysis of the Late Cenozoic faults and folds. The investigated neotectonic structures are ranked with respect to the regional classification principles. Changes in the crustal stress–strain state in the lithospheric plate boundaries between the Eurasian, North American, and Okhotsk Sea Plates are analyzed, and regularities of such changes are discovered. A set of models has been constructed for the studied segments of plate boundaries with account of the dynamics of the regional geological structures. The models can give a framework for the assessment of potential seismic risks of seismogenerating structures in the Russian Arctic region.